Hematological Alterations Induced by Zinc Oxide Nanoparticles and Preventive Role of Moringa Oleifera: In vivo - Samed Abduljabbar Ramadhan (Institute of Medico-legal Publications Pvt Ltd, 2021)
Increasing applications on nanomaterials have raised concerns about the toxicity of these materialstoward human health. This study aims to illustrate the effects of Zinc Oxide Nanoparticles (ZnONPs) onhematological parameters in rats and to explore the protective action of Moringa oleifera (MO) againsthematological changes induced by ZnONPs in rats. In our study, (24) albino rats were divided into fourgroups (6 for each group) and used. The studied rats included rats which received 100 mg/Kg ZnONPs for60 days , while the control group were rats without treatment. In the ZnONPs+MO group, rats were coadministered with a combination of ZnONPs at a 100mg/kg dose with MO at a 300 mg/kg dose for 60 days.The MO group animals were treated with 300 mg/kg of MO for 60 days. The animals were sacrificed andblood samples were obtained by cardiac puncture in the end of the experiments. Various blood parameterswere measured using HORIBA-Medical automatic hematology analyzer. Rats treated with ZnONPs showeda significant decrease (p<0.05) in red blood cell counts (RBCs), hemoglobin (Hb) concentration, meancorpuscular volume (MCV), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobinconcentration (MCHC), hematocrit value (Hct), and platelet count (Plt) count, except white blood cell count(WBCs) in comparison to the control group. Then, co-administration of M. Oleifera along with ZnONPsexerted a significant recovery effect in hematological disorders. Thus, these consequences established thatM. Oleifera shown a defensive impact against ZnONPs induced hematological alterations in male rats.